Implementation of the Tapak Suci Extracurricular Program to Instill Discipline and Humility in Social Interaction at TK ABA 57 Surabaya - Ulil Raras Ramadhani (Universitas Negeri Surabaya, 2026)
Character education in early childhood is the primary foundation for forming a noble personality (akhlakul karimah). This research aims to describe the implementation of the Tapak Suci extracurricular program in instilling discipline and humility in early childhood at TK Aisyiyah Bustanul Athfal 57 Surabaya. This study uses a qualitative approach with a case study method. Data collection techniques included participant observation, in-depth interviews, and documentation. Data analysis followed the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results indicate that Tapak Suci activities serve not only as physical exercise but also as a medium for internalizing character values through habituation, role modeling, and the reinforcement of religious values. The value of discipline is reflected in children's compliance with training rules, while the value of humility is evident in mutual respect and a lack of arrogance in interactions. Thus, Tapak Suci extracurricular activities are effective as a means of culture-based and religious character education for young children.